3) Resolva as equações: a) 2x²−5x−3=0 b)–2x² +3x+5=0 c) x²−4x+4=0 d) x²+3√2x+4,5=0 e) 4x−x(x−4)=−9
Soluções para a tarefa
Respondido por
4
Resposta:
Explicação passo-a-passo:
a) 2x²-5x-3=0
Aplique a fórmula de Bhaskara
a= 2 b= -5 c= -3
Δ= b²- 4 × a × c
Δ= (-5)² - 4 × 2 × (-3)
Δ= 25 + 24
Δ= 49
x= -b ± √Δ / 2 × a
x= -(-5) ± / 2 × 2
x= 5 ± 7 / 4
x1= 5 - 7 / 4
x1= -2 / 4
x2= 5 + 7 / 4
x2= 12/4
x2= 3
S= {-2/4 , 3}
b) -2x²+3x+5=0
a= -2 b= 3 c= 5
Δ= b²- 4 × a × c
Δ= 3² - 4 × (-2) × 5
Δ= 9 + 40
Δ= 49
x= -b ± √Δ / 2 × a
x= -3 ± / -4
x= -3 ± 7 / -4
x1= -3 - 7 / -4
x1= -10/-4
x1= 2,5
x2= -3+7/-4
x2= 4/-4
x2= 1
S= {2,5 , 1}
c) x²-4x+4=0
a= 1 b= -4 c=4
Δ= b²- 4 × a × c
Δ= (-4)² -4 × 1 × 4
Δ= 16 - 16
Δ= 0
x= -b ± √Δ / 2 × a
x= -(-4) ± / 2 × 1
x= 4 / 2
x= 2
S= {2}
Perguntas interessantes
Matemática,
9 meses atrás
Filosofia,
9 meses atrás
Inglês,
1 ano atrás
Ed. Física,
1 ano atrás
Ed. Física,
1 ano atrás
História,
1 ano atrás